2016
DOI: 10.17125/plaid.2016.65
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Benefits and Barriers to the Diabetes Prevention Program

Abstract: Objective: Diabetes prevention interventions have a proven positive effect on health outcomes. The goal of this project is to understand the factors that motivate and deter people with prediabetes from utilizing evidence-based education programs, such as the Diabetes Prevention Program (DPP).Research Design and Methods: Formative research was conducted among program facilitators, health providers who care for diabetes patients, and patients living with prediabetes to generate an in-depth understanding of perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 1 publication
1
11
0
Order By: Relevance
“…12,14 However, despite offering greater accessibility and sustainability, 15 community-based DPIs still require face-to-face delivery, which present participation barriers such as transportation, family/work commitments, and cost. 16,17…”
Section: Introductionmentioning
confidence: 99%
“…12,14 However, despite offering greater accessibility and sustainability, 15 community-based DPIs still require face-to-face delivery, which present participation barriers such as transportation, family/work commitments, and cost. 16,17…”
Section: Introductionmentioning
confidence: 99%
“…The perception of lack of time and resources is consistent with reported barriers to HPWP across different health care practice settings and disciplines. 29,37,[49][50][51][52] However, the perceived lack of patient interest is not consistent with the literature. Black et al 53 found that patients believed that engaging with PTs in personal discussions of physical activity, weight management, and smoking was appropriate.…”
Section: Discussionmentioning
confidence: 68%
“…The program length of one-year was not regarded as a barrier, as has been reported for the National Diabetes Prevention Program, and participants conveyed the satisfaction resulting from peer and program support as they could share their feelings, issues and struggles in a non-judgmental environment, foster peer support and encouragement, and accountability from Health Coaches [ 34 ]. The benefits of the long-term program format also allowed for incremental behavioral change and continuous feedback and support for behavior modification.…”
Section: Discussionmentioning
confidence: 99%